A study of C-reactive protein, lipid metabolism and peripheral blood to identify a link between periodontitis and cardiovascular disease. (November 2014) - Sharma, A; Astekar, M; Metgud, R; Soni, A; Verma, M; Patel, S
Abstract: Periodontitis is characterized by systemic inflammatory host responses that may contribute to a higher risk for cardiovascular disease. We hypothesized that periodontitis may be associated with altered C-reactive protein levels, serum levels of lipids and peripheral blood counts, and that these characteristics may serve as markers for a link between periodontitis and cardiovascular disease. Sixty subjects, 25–60 years old, were divided into three groups of 20 subjects each. Group 1, age and sex matched healthy controls; group 2, patients diagnosed with chronic periodontitis; group 3, patients diagnosed with acute periodontal lesions including periodontal abscess and pericoronal abscesses. Serum C-reactive protein levels, lipid levels and peripheral blood counts were obtained for all three groups. Significant increases in C-reactive protein and serum lipid levels, and altered peripheral blood counts were observed between the experimental groups; these factors were correlated with chronic periodontitis and cardiovascular disease. These simple, economical clinical measurements can be used to assess periodontal tissue damage and may be useful for predicting risk of cardiovascular disease in these subjects.